How depictive representations mandate pretence by being recognised in terms of what they depict - Neuber, Simone (Proceedings of the European Society for Aesthetics, 2012)
It is common knowledge within the theory of depiction that recognitional and make-believe accounts are two distinct and alternative approaches to depiction. My paper wishes to propose an alternative how we ought to think of the relationship between these two accounts. By presenting a theoretical account along Husserlian and Kantian lines, it is my hope to show that we can ground pretence in recognition of a certain kind. Thereby, we might avoid the unsatisfying allusion to automatic pretence, which Kendall Walton suggests, and instead replace it with a speciﬁc kind of anomalous recognition that can be a motivation for non-automatic and deliberate pretence. By alluding to an anomaly in the recognitional process, the account remains true to the distinct phenomenology of picture perception and is not forced to neglect the fact that recognition undergoes a certain and crucial modiﬁcation when talking about representational or depictive encounters only.
Gesehen am 19.03.2020